Methyl 4-[5-(4-fluorophenyl)-4-(pyridin-4-yl)-1H-imidazol-2-ylsulfanyl]butanoate - Koch, Pierre (International Union of Crystallography, 2008)
The title compound, C(19)H(18)FN(3)O(2)S, was synthesized in the course of studies on 2-alkylsufanylimidazoles as p38 mitogen-activated protein kinase inhibitors. The synthesis was achieved by nucleophilic substitution of 4-(4-fluorophenyl)-5-(pyridin-4-yl)-1,3-dihydroimidazole-2-thione with methyl 4-bromobutanoate. The five-membered heterocycle makes dihedral angles of 32.4 (2) and 18.3 (2)° with the fluorophenyl and pyridinyl rings, respectively, indicating a low degree of conjugation between these rings. Intramolecular C—H⋯N and intermolecular N—H⋯N hydrogen bonds as well as C—H⋯π interactions seem to be effective in stabilization of the crystal structure.